O05 The distribution of liver disease and associated risk factors in a large UK city. (20th September 2022) - Parker, Richard; Taylor, Adam; Dukes, Rachel; Wilks, Benjamin; Burn, Dan; Rowe, Ian
Abstract : Introduction: Liver-related deaths are increasingly common in the UK and are particularly frequent amongst people of working age. Understanding the risk factors for liver disease and their distribution is necessary to allow for targeted public health and hepatology interventions to improve health. We aimed to describe the distribution of population-level risk factors for liver disease and current practice regarding liver testing in a large UK city. Methods: Leeds is a large city of approximately 900, 000 people in England with a single hospital provider, which also provides laboratory services to primary care. Lower super output areas (LSOA), geographical units of approximately 1500 people, were used as the unit of analysis. Severe liver disease (LD) was quantified from clinical coding of hospital admissions with liver disease over a two year period from January 2018 to December 2019. The number of liver blood tests (LBT) over the same period were quantified for each LSOA. Publically available data regarding deprivation, obesity, diabetes, and alcohol use for each LSOA were collated and compared to the incidence of liver disease. The relationship between the various public health measures, LBT and LD was analysed with linear regression. Distribution of disease and risk factors was visualised with maps and panel plots. Results: Incidence of severe liver disease was not uniform across Leeds but showed significant variation across LSOA ranging between 1 – 199 admissions over the study period. Hazardous alcohol use (AUDIT score ≥ 16) (OR 2.80, p=0.037), severity of deprivation (OR 1.76 p<0.001) and obesity (odds ratio (OR) 1.13, p<0.001) were independent predictors of the incidence of severe liver disease. These risk factors clustered together geographically. Testing for liver disease with LBT was not associated with the incidence of liver disease or with the risk factors for liver disease and in fact was more frequent in areas of low disease prevalence. Discussion: Deprivation, obesity and alcohol use, measured at a population level are associated with liver disease and tend to occur together. These findings underline the need for robust public-health solutions to reduce the prevalence of liver disease and suggest that case-finding undiagnosed liver disease could be targeted to areas of high prevalence.